ANOMIE DAN KECENDERUNGAN PERILAKU AGRESIF DI KALANGAN REMAJA - Atamimi, Nuryati (Faculty of Psychology, Universitas Gadjah Mada, 1998)
Anomie is a condition in which there are no longer dominant values which affect one's behavior, or there is a lock of norms. For example, there is avague understanding toward sins and merits, or good and bad. Whereas aggressive behaviour which tends to harm oneself or one's environment.This study aimed at revealing the anomie level among teenagers, in relation to their tendency to behave aggressively.This study is also aimed at comparing the anomie level and the tendency to behave aggressively among teenagers living in big cities with the anomie level of those living in small towns, and among male and female teenagers.